Noninferiority of a Task-Shifting HIV Care an Treatment Model Using Peer Counselors and Nurses Among Ugandan Women Initiated on ART: Evidence From a Randomized Trial - Fowler, G. Mary (Lippincott Williams & Wilkins, 2013)
Objective: To assess the noninferiority of a task-shifting HIV treatment model relying on peer counselors and nurses compared with a physician-centered model among HIV-1-positive women initiated on antiretroviral therapy (ART) at a prevention of motherto-child transmission clinic in Mulago Hospital, Uganda. Methods: HIV-1-infected ART eligible naive women were randomized to either nurse–peer (intervention) or doctor–counselor (standard model) arm. The primary endpoint was virologic success defined attaining a viral load , 400 RNA copies per milliliter 6–12 months after ART initiation. Noninferiority was defined as the lower 95% confidence limit for the difference in proportions with virologic success being less than 10%. Secondary outcomes included immunologic success (mean CD4 count increase from baseline) and pill count. Results: Data on 85 participants were analyzed (n = 45 in the intervention and n = 40 in the standard model). The proportion of participants with virologic success was similar in the standard and intervention models [91% versus 88% respectively; difference, 3%; 95% confidence interval (CI): 211% to 12%]. Probability of viral detection at 6–12 months’ time point was similar in the 2 models(log-rank test P = 0.73). Immunologic and pill count indicators were also similar in the intervention and standard models, with mean CD4 increase of 217 versus 206 cells per microliter (difference, 11; 95% CI: 260 to 82 cells/mL) and pill counts of 99.8% versus 99.7% (difference, 0.0; 95% CI: 25% to 5%) respectively. Conclusions: Nurses and peer counselors were not inferior in providing ART follow-up care to postpartum women, an approach that may help deliver treatment to many more HIV-infected people.
Keywords: HIV; Adherence; Task-shifting; Antiretroviral therapy; Nurses; Peers; Intervention